PENGARUH WORK LIFE BALANCE TERHADAP KEPUASAN KERJA DENGAN BURNOUT SEBAGAI VARIABEL INTERVENING PADA PEGAWAI BALAI WILAYAH SUNGAI KALIMANTAN IV SAMARINDA - Suyanto; Syafarliddin Syachrani; M. Ibnu Rahmadan (OBOR: Oikonomia Borneo, 2025)
This study uses a quantitative approach with the aim of analyzing causal relationships based on hypotheses that have been formulated using the SPSS analysis tool. The sample in this study consisted of 143 employees of the Kalimantan IV Samarinda River Region Office. Data collection was carried out through interviews and questionnaires. To answer the formulation of the problem in the study, the data obtained were analyzed using the path analysis method. The results of this study revealed that Work Life Balance has an effect on job satisfaction through Burnout. In other words, the balance between work life of employees of Balai Wilayah Sungai Kalimantan IV Samarinda is classified as good, so that it has a positive impact on increasing their job satisfaction.